PENGARUH TEKNOLOGI INFORMASI DAN MOTIVASI TERHADAP KINERJA: TINJAUAN LITERATUR - Laura Komala; Ibrahim Bali Pamungkas; Nanda Rodiyana (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The purpose of this research is a) to identify the influence of information technology on performance based on empirical studies in the last 6 years, and b) to identify the influence of motivation on performance based on empirical studies in the last 6 years. The method of searching for article sources was carried out through the GARUDA database (2017-2022) to retrieve relevant articles published in Indonesian. Keywords related to information technology and motivation towards performance were reviewed from the abstract or text of research journals before being included in the review according to the criteria. Based on the review of 6 journals over the last 6 years, the results show that the review of all 6 research journals indicates a positive and significant partial influence of information technology and motivation on performance.